Goal and behavior setting: The structured and unstructured self-regulation model - Victorino, Luiz (Seven Editora, 2024)
Self-regulation, the ability to control our thoughts, emotions, and behaviors, is critical to success in many areas of life. This paper investigates the neural mechanisms underlying this complex ability, focusing on goals, priming, and the SUSR (Structured and Unstructured Self-Regulation) model. Initially, the neural bases of self-regulation are explored, highlighting the brain regions involved in planning, inhibitory control and decision-making. The importance of goals as guides to action is emphasized, and different types of goals (short-term and long-term, specific and general) are discussed. Clear goal setting and consistent pursuit are presented as crucial for effective self-regulation. The concept of priming, i.e., the activation of concepts or ideas in the mind that influence subsequent behavior, is introduced. Studies show that priming can modulate self-regulation, either facilitating or hindering the achievement of goals. The article discusses how priming can be used to promote more adaptive behaviors. Finally, the SUSR model is presented as a theoretical framework to understand the processes of self-regulation. This model distinguishes between structured self-regulation, which involves the planning and execution of actions in a deliberate manner, and unstructured self-regulation, which occurs more automatically and habitually. The SUSR model offers a comprehensive perspective on the different levels of cognitive control involved in self-regulation. DOI:https://doi.org/10.56238/sevened2024.026-048